A comprehensive review on research developments of vegetable-oil based cutting fluids for sustainable machining challenges. (July 2021) - R., Sankaranarayanan; N., Rajesh Jesudoss Hynes; J., Senthil Kumar; Krolczyk, G.M.
Graphical abstract: Abstract: In the present environmentally conscious world, there is a paradigm shift from using harmful cutting fluids to bio-oil based cutting fluids in machining applications. Vegetable oils, as potential eco-friendly metal cutting fluids offer striking solutions against various health hazards such as skin irritations, hazardous aerosols, ingestion, etc., caused by synthetic cutting fluids. The present work critically analyses the prospect of accomplishing sustainable green manufacturing through deployment of eco-friendly vegetable oil-based cutting fluids. The appropriateness of several vegetable oils is reviewed and compared for various metal cutting applications. This review of research article indicates that vegetable oils are capable of replacing synthetic cutting fluids and this alternative could help in effective and economical means towards achieving green machining.